MODERN TRENDS IN THE DEVELOPMENT OF THE INSURANCE MARKET IN UZBEKISTAN - Eldor Nozimov; Sherbek Qurbonov (Modern American Journals, 2025)
This article examines the modern trends in the development of the insurance market in Uzbekistan, focusing on the key drivers, regulatory reforms, and structural transformations observed in recent years. The study highlights the growing role of digitalization, the expansion of innovative insurance products, and the increasing participation of private insurance companies in enhancing market competitiveness. Particular attention is given to the evolution of compulsory and voluntary insurance segments, the improvement of risk management practices, and the influence of international standards on the national insurance system. The research findings demonstrate that effective policy measures, technological integration, and stronger institutional capacity are crucial for ensuring sustainable growth and strengthening the financial stability of the insurance sector in Uzbekistan.
Keywords: Insurance market, Uzbekistan, digitalization, financial stability, innovative insurance products, regulatory reforms, risk management, compulsory insurance, voluntary insurance, market development.